Introduction to the Special Issue of “TikTok and Social Movements” - Lee, Jin; Abidin, C. (SAGE PUBLICATIONS LTD, 2023)
This Special Issue of “TikTok and Social Movements” emerges from an attempt to map out the landscape of social movements happening on TikTok, drawing from the online symposium “TikTok and Social Movements” hosted in September 2021 by the TikTok Cultures Research Network, a research portal for interdisciplinary scholarship on TikTok cultures. The recent growing popularity of TikTok has transformed the cultures and practices of social movements worldwide. Through the platform’s participatory affordances, many users find meaningful ways to engage with the platform and its cultures, by leading and participating in a variety of activist initiatives for global awareness, social change, and civic politics. Within this context, this introduction to the Special Issue titled “TikTok and Social Movements” begins by thinking about how social media pop cultures have served as a vehicle for mobilizing and engaging in social movements for social (in)justice and politics in the era of social media. By situating TikTok, a nascent platform and culture of short video, within the ongoing discussion of digitally mobilized movements and social justice, this introduction addresses several crucial points to consider when discussing TikTok cultures and social movements that are happening or interrupted on the platform. These points are interrogated with more details and cultural contexts in the five case studies and three expert commentaries in this Special Issue. Specifically, the collection of papers interrogate how TikTok’s interactive and creative affordances have augmented and altered our cultures, practices, politics, and power dynamics of engaging with publics for various beliefs and social agendas.